1957
DOI: 10.1002/aja.1001010203
|View full text |Cite
|
Sign up to set email alerts
|

Sites of protein synthesis as shown by radioautography after administration of S35–labelled methionine

Abstract: and Oniocrdlg o f Waxkington, Seallle, Wmhinglon THIRTY-TTIBEE FIQURERSITES OF PUOTEII SYNTHESIS 227 yeast was added t,o 9 parts of the prepared diet formula arid then the expected weight gain was observed ( fig. 1). A few of the animals w-cre used in pilot expcrimcnts. The others werc treated as indicated below.'For radioa2~ictogru,phic observu.tions, DL-methionine-S35 (specific activity, 1 mc per 10.3 mg) 1va.s injoctcxi subcutaneously, 7.7 vc (0.0793 mg of methionine) per gram of body weight, 4 weeks after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

1958
1958
1971
1971

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(24 citation statements)
references
References 35 publications
0
21
1
2
Order By: Relevance
“…The heavy concentration of label in the proliferative cells of the crypts in jejunum and colon indicates rapid protein synthesis in the proliferating cells. With both leucine (8) and methionine (2), the labeling over proliferative cells is much heavier than over mature cells. The disappearance of label from the proliferative zones can be accounted for by emigration of labeled cells and continued protein synthesis from endogenous precursors.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy concentration of label in the proliferative cells of the crypts in jejunum and colon indicates rapid protein synthesis in the proliferating cells. With both leucine (8) and methionine (2), the labeling over proliferative cells is much heavier than over mature cells. The disappearance of label from the proliferative zones can be accounted for by emigration of labeled cells and continued protein synthesis from endogenous precursors.…”
Section: Discussionmentioning
confidence: 99%
“…During normal nutrition the small intestine has a very rapid rate of protein synthesis (3,9,10,28), and this synthesis rate is not slowed markedly during protein depletion (3,11,21,24). After prolonged protein starvation parenterally administered radioactive amino acids are incorporated into the protein of the small intestinal mucosa to a greater extent than in any other organ (8,11,21).…”
Section: First Experimentsmentioning
confidence: 99%
“…In the earlier studies of the effect of protein depletion upon the incorporation of radioactive amino acids into intestinal mucosal protein, the amino acids were always given intraperitoneally (3,8,10,11,21) and it was found that there was more incorporation of the amino acid into small intestinal protein than in other tissues, and more than in the protein-fed animals. In the present study, oral administration of the amnino acid showed an even greater difference between protein-deprived and control animals.…”
Section: First Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques (Leblond et a^., 1957) are based on the fact that the first sites to become radioactive after injection of a labelled amino acid are those places where protein synthesis takes place. The radioactivity appearing later at other sites can be due to migration of the newly synthesized proteins (Warshawsky et , 1963).…”
Section: Ultrastructure Of Secretionmentioning
confidence: 99%